STRATEGI PENGEMBANGAN UMKM SEBAGAI UPAYA PEMULIHAN EKONOMI DI DESA PARUNGSEAH - Rahmat Hidayat; Rizalul Fadilah; Detiya Setiyani Putri; Intan Nurkamila; Lia Yuliani; M.Wisnu Apriandi (LPPM Politeknik Pajajaran ICB Bandung, 2023)
Student Work Class (KKM) is a form of community service carried out by students in an interdisciplinary, institutional, and partnership manner as one of the manifestations of STIE PASIM SUKABUMI. The community service program is seen as a program that must be implemented, both by lecturers and by students, based on the principles of academic, entrepreneurial, and professional competence, so as to produce quality, relevant, and synergistic community service programs in improving community empowerment. This study aims to analyze the development of MSMEs in efforts to restore the economy in Parungseah Village. This study prioritizes the use of methods that are appropriate to the subject matter of the research being conducted, in order to obtain relevant data for further discussion. This research is intended to obtain an overall picture of the development of micro, small and medium enterprises (MSMEs) through external party facilitation and internal potential in the Parungseah Village business group. The efforts made in the MSME development strategy as an effort to restore the economy in Parungseah Village are the ease access to capital, assistance in developing business infrastructure, developing business scale, developing business networks, marketing and business partnerships, increasing access to technology, and developing human resources